Chronic exposure to environmentally relevant concentration of abamectin induces gut toxicity in largemouth bass: Molecular fate, bioaccumulation risk and its potential phytoremediation - Rabia Tahir; Haoxiao Yan; Kuo He; Abhimanyu Shrestha; Hao Liu; Quanxi Li; Jin Mu; Zaizhao Yang; Lipeng Guo; Chengxian Zhang; Zhihong Li; Liulan Zhao; et al. (Environmental Chemistry and Ecotoxicology)
Abamectin (ABA), one of the most extensively used pesticides, has been increasingly detected in aquatic environment, thereby posing a continuous exposure risk to edible fish. Although organisms are exposed to various pollutants through gut, yet toxic effects of ABA on gut health remain unclear. Henceforth, our study investigated ABA-induced gut toxicity in largemouth bass, widely consumed fish, at environmentally relevant concentration. Chronic exposure of six weeks caused severe tissue damage, including vacuolation, and goblet cell exudation. The reduction of antioxidant enzymes (SOD, GSH-Px and CAT) was triggered by surge in ROS level, resulting in lipid peroxidation (MDA) and dysregulation of pgc-1α, keap1, and nrf2. Disruption in tight junctions (claudin-5, −7, occludin, and zo-1) weakens the gut's protective barrier. Inflammatory response characterized by NF-κb-mediated IκBα degradation, leading to increased cytokines (il-8, il-10, il-15, il-1β, tgf-β1, and tnf-α), and suppressed immunity (ACP and AKP). Dysregulated translation and transcription level of bax, bcl-2, tnfr1 and caspases indicated the apoptosis. Excessive autophagic flux, evidenced by increased autophagosome formation by upregulation of atg's and lc3ii, p62 degradation, and suppression pi3k, mtor, and akt. HPLC-UV and IBR analysis further confirmed the exposure risk by revealing significant ABA bioaccumulation in gut tissues, indicating its persistent retention. Molecular docking validated that ABA binds to superoxide dismutase isoforms and AKT via hydrogen bonding and hydrophobic interactions. In contrast, aforementioned phenomena were effectively modulated by curcumin (CUR) supplementation by regulation of key biomarkers. Altogether, it highlighted the necessity of including edible fish in regulatory decisions concerning pesticide use.